Convergence over space and generations in the post-apartheid South Africa - Yamauchi, Futoshi (2006)
This paper examines a range of historical and location factors that determine the quality of public school education in post-apartheid South Africa. Empirical analysis shows that population groups are still spatially segregated due to the legacy of apartheid, and given school quality is positively correlated with school fees, quality education is concentrated in formerly white, coloured and Indian schools in areas where the majority is non-African. Even after the abolishment of apartheid, the imperfect credit market has prevented Africans from moving into well-off residential areas where they could access quality education.Historical factors,however,are less important in metropolitan areas where the inflow of population is large. To address this imbalance, financial support to disadvantaged locales and schools should be strengthened.